Oral health conditions among the elderly in Southeastern São Paulo State (Journal of Applied Oral Science, 2009)
OBJECTIVE: This study aimed to asses oral health conditions in a population aged 60 years and over living in Botucatu, Southeastern Brazil. A cross-sectional population-based study was carried out using a random sample (N=372) of the urban population aged 60 years and over from the city of Botucatu, in 2005. World Health Organization criteria and codes for oral health epidemiological surveys were used. Re-examination was carried out in 10% of individuals aiming to evaluate intra-examiner agreement. Statistical analysis was performed by one-way ANOVA or Kruskal-Wallis ANOVA, as applicable. Also, the t-test was used in the absence of homoscedasticity. Fisher's exact test was used for situations where the categories with less than five units were observed. Adjusted residuals and multiple-comparison analysis were conducted to identify associations between variable categories and subgroups. The intra-examiner agreement was 98% and Kappa statistics result was 0.95. Loss component represented 90.68% of DMF-T index, which was 29.85. The prevalence of edentulism was 63.17%. Upper and lower dentures were found in 80% and 58% respectively, with complete denture as the most commonly used. In those studied, 15% required upper and 38% lower dentures. There was more need for complete denture in both jaws. Approximately 20% had soft tissue alterations. For periodontal conditions, most sextants were excluded (81.81%). Periodontal pockets (4 - 5 mm) were seen in 11.29% of the examined individuals. The oral health status of the elderly population in Botucatu is poor, as well as in other Brazilian cities. The results of this study may help planning collective health actions, giving an accurate description of the oral problems among the elderly.